Monkey Trouble The Scandal of Posthumanism - Peterson, Christopher (Fordham University Press, 2017)
Engaging with recent theoretical developments in speculative realism and object oriented ontology, ape and parrot language studies, along with literary texts by J.M. Coetzee, Charles Chesnutt, and Walt Whitman, and films by Alfonso Cuarón and Lars von Trier, Monkey Trouble argues that the turn toward immanence in contemporary posthumanism promotes a cosmocracy that absolves one from engaging in those discriminatory decisions that condition hospitality as such. Anthropocentrism cannot be displaced through a logic of reversal that elevates immanence above transcendence, horizontality over verticality. This decentering must cultivate instead a human/nonhuman relationality that affirms the immanent transcendency spawned by our phantasmatic humanness.